2019
DOI: 10.1021/acs.inorgchem.9b00202
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Semiconductor Oxide and a Microporous (3,10)-Connected Co6-Based Metal–Organic Framework for Enhanced Oxygen Evolution Reaction

Abstract: Developing high-efficiency and cost-effective electrocatalytic oxygen evolution reaction (OER) catalysts would determine the future distributions of energy conversion technologies. Metal–organic frameworks (MOFs), with unsaturated active metal sites, functionalized organic linkers, and large surface areas, are emerging heterogeneous electrocatalysts for the water oxidation process. Herein, we report an oxygen-evolving microporous (3,10)-connected Co6-based MOF (denoted as CTGU-14) for the electrocatalytic OER.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(24 citation statements)
references
References 45 publications
2
22
0
Order By: Relevance
“…Although it is a huge challenge to successfully assemble the targeted porous Ln-MOFs, their excellent properties in the aspects of selective separation and storage, luminescence and recognition, and catalysis continue to attract remarkable attention from many scientists. Especially, the fact that the rich coordination geometry of Ln 3+ ions due to the ratio of charge to radius (Z/R) and abundant hybrid orbitals of f n d 2+m sp 3 (n = 0−3, m = 1−3) gives them a wide coordination number range, which grants octa-or nonacoordinated Ln 3+ ions the ability to polarize small guest molecules, such as CO 2 , SO 2 , and H 2 S. 20,21 Recently, one porous Eu-MOF reported by Zhao and coworkers exhibited an efficient catalytic performance for the chemical fixation of CO 2 , 22 which confirmed that Ln-MOFs are subjects worthy of study due to the fact that the high coordination characteristics of Ln III ions give them ideal Lewis acid sites. Therefore, the exploration of syntheses and optimization for Ln-based host skeletons by increasing highly active sites to achieve targeted catalysts has become inevitable.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Although it is a huge challenge to successfully assemble the targeted porous Ln-MOFs, their excellent properties in the aspects of selective separation and storage, luminescence and recognition, and catalysis continue to attract remarkable attention from many scientists. Especially, the fact that the rich coordination geometry of Ln 3+ ions due to the ratio of charge to radius (Z/R) and abundant hybrid orbitals of f n d 2+m sp 3 (n = 0−3, m = 1−3) gives them a wide coordination number range, which grants octa-or nonacoordinated Ln 3+ ions the ability to polarize small guest molecules, such as CO 2 , SO 2 , and H 2 S. 20,21 Recently, one porous Eu-MOF reported by Zhao and coworkers exhibited an efficient catalytic performance for the chemical fixation of CO 2 , 22 which confirmed that Ln-MOFs are subjects worthy of study due to the fact that the high coordination characteristics of Ln III ions give them ideal Lewis acid sites. Therefore, the exploration of syntheses and optimization for Ln-based host skeletons by increasing highly active sites to achieve targeted catalysts has become inevitable.…”
Section: ■ Introductionmentioning
confidence: 99%
“…2 , the maximum absorption of CO 2 at 273 K and 298 K was 93.44 cm 3 g −1 and 64.99 cm 3 g −1 , respectively, which are higher than that in the literature, such as for NUC-5, MOF-5, and Uio-66. 18 Simultaneously, incomplete adsorption isotherms and CO 2 desorption lead to a moderate hysteresis loop, which confirms the strong interaction between the host and guest. Furthermore, in quantify the binding force between the CO 2 molecules and the framework of NUC-30, Q st was calculated using the virial method with the resulting value at zero coverage being 25.8 kJ mol −1 , which implies that the adsorbed CO 2 molecules can be easily released, allowing the host framework of NUC-30 to be regenerated, as shown in Fig.…”
Section: Resultsmentioning
confidence: 73%
“…Moreover, the peak at 530.9 eV probably belongs to a high number of oxygen vacancies (O v ), which is attributed to the breaking of NiO bonds after etching treatment. [ 31 ] It should be noted the oxygen vacancies is favorable for decreasing the adsorption energy of intermediates and facilitating the desorption of intermediates on active sites in electrocatalysis. [ 28,32 ]…”
Section: Resultsmentioning
confidence: 99%